Pillars of peace : images of President Obasanjo's peace and reconciliation activities in Africa - Omotosho, Funsho (Ibadan: Netview Books, 2007)
The book is a documentation for posterity of the immense contributions of Chief Olusegun Obasanjo to the struggle for peace and security in Africa.
Includes bibliographical references
as 23/07/2019
Nigeriana
Keywords: Olusegun Obasanjo; Peace-building; Security, International; International relations--Administration; International relations; Peacekeeping forces, Nigerian; Africa; Nigeria